Separation of nanoscale natural fibers from rice straw by organosolv-high shear homogenization system - Narkchamnan, Siritorn; Krongtaew, Chularat (Asia-Pacific Journal of Science and Technology, 2017)
The purpose of this study was to produce nanoscale natural fi bers from rice straw (Triticum sativum) by using organosolv-high shear homogenization system. Rice straw was subjected to alkaline solution in the presence of ethanol as a solvent using a central composite design (CCD). Infl uencing factors in CCD included sodium hydroxide concentration, volumetric ratio of ethanol to water and treatment duration. Optimization results showed that the optimum condition of cellulose fi bers separation for highest purity and minimum weight loss was 20.24%(w/w) sodium hydroxide and 37.94%(v/v) ethanol for 15.39 h at room temperature. The cellulose content from that condition was 86.61%(w/w) and weight loss was 44.51%. Separated fi bers after high shear homogenization was analyzed by Fourier transform infrared spectroscopy (FT-IR) and Transmission electron microscopy (TEM). Diameters of natural fi bers were in nanoscale ranging from 5 to 40 nm.